Answer:
(a+b)(c+d)=a c+a d+b c+b d is the formula
Step-by-step explanation:
Answer:
ok, te ayudaré
94÷4=23.5
535÷5=107
76÷3=25.33333333333
829÷4=207.25
26÷9=2.8888888889
569÷8=71.125
97÷9=10.7777777778
527÷3=175.6666666667
25÷4=6.25
534÷9=59.3333333333
58÷6=9.6666666667
37÷5=7.4
49÷2=24.5
156÷6=26
I hope it serves you, give me a crown please
Answer:
yes
Step-by-step explanation:
I know the correct answer but I need you to answer my questions first
Answer:
B. 5.2
Step-by-step explanation:
<em><u>:-[ </u></em><em><u>y</u></em><em><u>o</u></em><em><u>u</u></em><em><u> </u></em><em><u>w</u></em><em><u>i</u></em><em><u>l</u></em><em><u>l</u></em><em><u> </u></em><em><u>k</u></em><em><u>n</u></em><em><u>o</u></em><em><u>w</u></em><em><u> </u></em><em><u>t</u></em><em><u>o</u></em><em><u> </u></em><em><u>h</u></em><em><u>a</u></em><em><u>v</u></em><em><u>e</u></em><em><u> </u></em><em><u>b</u></em><em><u>r</u></em><em><u>a</u></em><em><u>i</u></em><em><u>n</u></em><em><u>l</u></em><em><u>y</u></em><em><u>:-) </u></em>